A Review of Coagulation Abnormalities of Autoimmune Acquired Factor V Deficiency with a Focus on Japan - Ichinose, Akitada; Osaki, Tsukasa; Souri, Masayoshi (Seminars in Thrombosis and Hemostasis, 2021)
Coagulation factor V (or FV for the purpose of medical safety) is an essential cofactor of coagulation factor X in the common pathway of coagulation; severe FV deficiency leads to a bleeding tendency. Although both congenital and acquired FV deficiencies are widely recognized, FV deficiency also presents as an autoimmune disorder. A nationwide survey on autoimmune coagulation factor deficiencies (AiCFDs) conducted in Japan by our Japanese Collaborative Research Group identified 24 new patients with autoimmune FV deficiency (AiFVD) in the past 5 years. Furthermore, our extensive literature search confirmed that 177 AiFVD cases have been reported in previous articles published from Japan. Patients with AiFVD in Japan were predominantly men, with age similar to those with other AiCFDs. AiFVD was confirmed as a relatively mild type of bleeding diathesis, associated with lower mortality rate than that for AiFVD and other AiCFDs reported in previous studies. Patients with AiFVD had variable FV inhibitor titers and both neutralizing anti-FV autoantibodies and nonneutralizing counterparts. Although spontaneous resolution occurs in some patients, timely initiation of hemostatic and immunosuppressive therapies helps arrest the bleeding and eliminate anti-FV antibodies, resulting in a high cumulative recovery rate. Immunological anti-FV antibody detection is recommended to avoid missing AiFVD cases for the presence of nonneutralizing anti-FV autoantibodies. Further investigation is necessary to clarify the long-term prognosis and optimal management of AiFVD.
Keywords: acquired coagulation factor deficiency; autoantibody; bleeding disorder; factor V; inhibitor; nonneutralizing antibody